Удмуртолэнд: [кылбуръёс] / Куликовская Пелагея - Куликовская Пелагея (2022)
Экземпляры: УКП (20230227) / Инвентарный номер: АП20220300 / Сис.шифр: 84(2) / Авт.знак: К 90 / ГРНТИ: 17 / ББК: 84(2=664.1)-5